1993
DOI: 10.1159/000187521
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Concentration Profiles of Simvastatin 3-Hydroxy-3-Methylglutaryl-Coenzyme A Reductase Inhibitory Activity in Kidney Transplant Recipients with and without Ciclosporin

Abstract: A few cases of severe rhabdomyolysis have been reported in heart transplant recipients treated simultaneously with ciclosporin (CS) and the 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase inhibitor lovastatin. When measured, plasma lovastatin HMG-CoA reductase inhibitor concentrations in these patients were higher than expected. This prompted us to study the plasma concentration profiles of simvastatin HMG-CoA reductase inhibitory activity after a single dose of simvastatin in kidney transplant recip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(54 citation statements)
references
References 7 publications
3
51
0
Order By: Relevance
“…Several studies have reported that certain agents such as cyclosporine, calcium antagonists, and erythromycin that act as substrates for the cytochrome P450 isoenzyme CYP3A4 tend to show drug interactions with these statins. [16,17] It is suspected that competition between these agents and statins, both being CYP3A4 substrates, inhibits the action of CYP3A4 to eliminate substrate, and results in elevation of serum statin concentrations to toxic levels. The importance of the relation between serum statin concentration and adverse drug reactions is also supported by the evidence that statin-induced adverse effects occur dose-dependently.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that certain agents such as cyclosporine, calcium antagonists, and erythromycin that act as substrates for the cytochrome P450 isoenzyme CYP3A4 tend to show drug interactions with these statins. [16,17] It is suspected that competition between these agents and statins, both being CYP3A4 substrates, inhibits the action of CYP3A4 to eliminate substrate, and results in elevation of serum statin concentrations to toxic levels. The importance of the relation between serum statin concentration and adverse drug reactions is also supported by the evidence that statin-induced adverse effects occur dose-dependently.…”
Section: Discussionmentioning
confidence: 99%
“…Coadministration of HMG-CoA reductase inhibitors with CYP3A4 inhibitors/substrates such as itraconazole (16,17) and cyclosporine (1,11) significantly increases the levels of HMG-CoA reductase inhibitors in plasma. Simvastatin and lovastatin appear to be especially sensitive to P450 3A4 inhibition.…”
mentioning
confidence: 99%
“…[112][113][114] In the presence of cyclosporine (a potent inhibitor of OATP1B1 and CYP3A4) atorvastatin AUCs were 6-to 15-fold increased, [115][116][117] fluvastatin AUC was 3-fold increased, 118 lovastatin AUC was 20-fold increased, 119 pitavastatin AUC was 5-fold increased, 99 pravastatin AUC was 5-to 10-fold increased, 44,119,120 rosuvastatin AUC was 7-fold increased, 121 and simvastatin AUC was 3-to 8-fold increased. 122,123 Certainly, CYP3A4 inhibition from cyclosporine can contribute to the overall increases observed in statin exposure; however, this can be concluded to play a minor role given that rosuvastatin, pravastatin, and pitavastatin are not significantly metabolized by CYP3A4. [124][125][126][127][128] In fact, pravastatin, the most hydrophilic compound, had a 10-fold increase in AUC when administered to children and adolescents who were taking triple immunosuppressive therapy containing cyclosporine and no other CYP substrates.…”
Section: Distributionmentioning
confidence: 99%